The Simple and Traditional Game-Based Health Education Model to Promote Healthy Lifestyles in Elementary School Students: A Literature Review - Hijrah Maulidiah Afifah; Drastiana Siwi Maheswari; Kurnia Primaningsih (Universitas Negeri Semarang, 2025)
The purpose of this study is to obtain an appropriate theoretical basis related to simple and traditional game-based health education models for building healthy lifestyles among elementary school students. The research method used in this study is a literature review, in which the author collects data from previous studies related to the topic being researched. Data collection began with a literature search using several keywords, including “simple and traditional games,” “school health education,” “healthy lifestyle patterns among elementary school students,” and “play-based approach” on Google Scholar and Semantic Scholar. The collected journal articles were then read and processed to establish a theoretical foundation. The author identified 50 previous studies discussing the model of health education based on simple and traditional games to promote healthy lifestyles among elementary school students. Based on these findings, the author selected 15 (fifteen) journal articles as the primary review materials. The conclusion drawn from this study is that a health education model based on simple and traditional games is an effective and feasible strategy to implement, thereby fostering healthy lifestyle habits among elementary school students. Teachers and educators are encouraged to optimize the use of games as a learning medium to enhance students' knowledge, attitudes, and healthy behaviors, thereby fostering sustainable healthy lifestyles in the future.